HUBUNGAN PERILAKU PERSONAL HYGIENE DENGAN KEJADIAN KEPUTIHAN PADA REMAJA DI SMP MUHAMMADIYAH 1 GAMPING - Intan Okta Anggi Pratiwi; Nurul Mahmudah (Bajang Institute, 2025)
Background: According to the World Health Organization (WHO), in 2022, approximately 75% of adolescent girls worldwide experienced vaginal discharge at least once in their lifetime, and 45% experienced it twice or more. In Indonesia, 90% of women are at risk of experiencing vaginal discharge due to the country’s tropical climate, while in Europe, only 25% of women are affected. Based on data from the Yogyakarta Special Region Health Office (Dinkes DIY, 2016), there were 2.9 million adolescent girls in the region, and 68% of them experienced pathological vaginal discharge. Objective: This study aims to investigate the relationship between personal hygiene behavior and the incidence of vaginal discharge among adolescents at SMP (Junior High School) Muhammadiyah 1 Gamping. Method: This study employed a quantitative design with a correlational approach using a cross-sectional method. The sampling technique used was total sampling. The respondents consisted of 60 seventh-grade female students: 7 students from class VII A, 12 from class VII B, 13 from class VII C, 14 from class VII D, and 14 from class VII E. Data on personal hygiene behavior and the incidence of vaginal discharge were collected using a questionnaire. Data analysis was performed using the Chi-Square statistical test. Results: The results showed that among the 60 respondents, 44 students (73.3%) demonstrated good personal hygiene behavior, while 16 students (26.7%) had poor personal hygiene behavior. Vaginal discharge was reported in 20 students (33.3%), while 40 students (66.7%) did not experience it. Conclusion: There is a significant relationship between personal hygiene behavior and the incidence of vaginal discharge, with a p-value of 0.000 < 0.05